Relationship between Mercury Concentrations in Hair and Blood in Dene/Métis Communities of the Northwest Territories - Tang, Furong (University of Waterloo, 2019)
Background: Mercury (Hg) is a global environmental pollutant as well as a growing concern to public health. Indigenous populations in the Northwest Territories (NWT) may experience elevated Hg exposures due to higher consumption rates of fish compared to the Canadian general populations. Many biomonitoring projects are conducted to estimate human health risk caused by environmental Hg exposure; blood and hair are two of the most frequently used matrices for quantifying individual and population exposures. The association between Hg concentrations in hair and blood is often assumed to be linear with a hair-to-blood Hg concentration ratio of 250. However, this ratio varies among populations, and further research is needed to explore the relationship between Hg concentrations in hair and blood in Indigenous populations of the NWT. Objective: The objectives of this study are to: 1) examine the relationship between Hg concentrations in hair and blood and the reliability of the widely accepted hair-to-blood ratio of 250 within this study population; 2) further improve the relationship by the application of Multiple Imputation (MI) and by the inclusion of covariates in the imputation model; 3) assess the effectiveness of MI for addressing missing data and data below limit of detection (LOD) from biomonitoring studies. Methods: A community-based project was designed based on consultations that began in 2014. This contaminant biomonitoring project provided baseline reference Hg levels for the Sahtu region and the Dehcho region of the Northwest Territories. Blood and hair samples were collected for Hg exposure assessments. Participants were also asked to provide basic demographic information. Simple linear regression models were used to explore the relationship between Hg concentrations in hair and blood with complete cases across communities. MI was applied to impute the missing data and the data below LOD. Results: The association between Hg concentrations in hair and blood were found to be linear within communities. ...